Relationship Between the Weight of a Low Birth Agency With Justice in The Hospital Bhayangkara Kediri City - Dina Dewi Anggraini; Martha Kahi Juwa (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2020)
Jaundice is a yellow stain on the skin, sclera, or mucous membranes as a result of excessive accumulation of bilirubin in the tissues. Low birth weight babies (LBW) are defined as birth weight 2,500 grams or less. In infants with low birth weight can experience various complications, one of which is hyperbilirubinemia (jaundice). This study aims to determine the relationship of Low Birth Weight Babies (LBW) with the incidence of jaundice in Bhayangkara Hospital in the city of Kediri. The research design used is correlational analytic research. The method used is a cross sectional approach. The sampling technique was carried out in total sampling as many as 105 samples of infants with LBW. Research data is taken from medical records. Data were analyzed univariately and bivariately using Spearman's Rho test. The results of the study showed that out of 105 infants with low birth weight who experienced physiological jaundice as many as 75 infants (71.4%) and pathological jaundice as many as 30 infants (28.6%). The results of the Spearman Rh Rho test analysis showed that the p value = 0.067 or less than α = 0.05 (0.067 0.05), which means that H0 is rejected and H1 is accepted, meaning that there is a relationship between the incidence of LBW and neonatal jaundice in Bhayangkara Hospital in the City Kediri in 2018. The strength of the relationship is based on the correlation coefficient of 0.196 which means that there is a moderate relationship between the incidence of LBW and jaundice in Bhayangkara Hospital in Kota Kadiri in 2018.